Ikhtiyat in The Epistemology of Astronomy Fiqh: An Integration of Conservatism and Contextualism - Fauzi, Ahmad (International Tatho Academics, 2025)
The determination of the beginning of the Hijri month, especially in the context of Ramadan, Shawwal and Dhul Hijjah, is a crucial issue that often triggers differences of opinion among Indonesian Muslims. Nahdlatul Ulama (NU), through its Falakiyah Institute, uses a unique approach in determining the beginning of the month, namely by prioritising the principle of ikhtiyath (prudence). This principle is not only rooted in technical astronomical considerations, but also relies strongly on the rules of ushul fiqh and considerations of public good. This study aims to examine the concept of ikhtiyath theoretically in the perspective of Islamic fiqh and analyse its application in the practice of determining the beginning of the month by Falakiyah NU contextually. This research uses a qualitative method based on literature study on relevant writings and uses descriptive analysis. The results of this study found that ikhtiyath is an important methodological basis in maintaining the validity of worship and social religious stability, especially regarding the determination of the beginning of the lunar month. This finding confirms that NU's Falakiyah approach is not merely conservative, but has epistemological and contextual relevance in responding to modern religious challenges.